Regulatory T-cell deficiency leads to features of autoimmune liver disease overlap syndrome in scurfy mice - Yilmaz, Osman K.; Häberle, Stefanie; Kim, Yong Ook; Fritzler, Marvin J.; Weng, Shih-Yen; Goeppert, Benjamin; Raker, Verena; Steinbrink, Kerstin; Schuppan, Detlef; Enk, Alexander; Hadaschik, Eva (Frontiers in immunology, 2023)
IntroductionScurfy mice have a complete deficiency of functional regulatory T cells (Treg) due to a frameshift mutation in the Foxp3 gene. The impaired immune homeostasis results in a lethal lymphoproliferative disorder affecting multiple organs, including the liver. The autoimmune pathology in scurfy mice is in part accompanied by autoantibodies such as antinuclear antibodies (ANA). ANA are serological hallmarks of several autoimmune disorders including autoimmune liver diseases (AILD). However, the underlying pathogenesis and the role of Treg in AILD remain to be elucidated. The present study therefore aimed to characterize the liver disease in scurfy mice.MethodsSera from scurfy mice were screened for ANA by indirect immunofluorescence assay (IFA) and tested for a wide range of AILD-associated autoantibodies by enzyme-linked immunosorbent assay, line immunoassay, and addressable laser bead immunoassay. CD4+ T cells of scurfy mice were transferred into T cell-deficient B6/nude mice. Monoclonal autoantibodies from scurfy mice and recipient B6/nude mice were tested for ANA by IFA. Liver tissue of scurfy mice was analyzed by conventional histology. Collagen deposition in scurfy liver was quantified via hepatic hydroxyproline content. Real-time quantitative PCR was used to determine fibrosis-related hepatic gene expression. Hepatic immune cells were differentiated by flow cytometry.ResultsAll scurfy mice produced ANA. AILD-associated autoantibodies, predominantly antimitochondrial antibodies, were detected at significantly higher levels in scurfy sera. CD4+ T cells from scurfy mice were sufficient to induce anti-dsDNA autoantibodies and ANA with an AILD-related nuclear envelope staining pattern. Liver histology revealed portal inflammation with bile duct damage and proliferation, as in primary biliary cholangitis (PBC), and interface hepatitis with portal-parenchymal necroinflammation, as found in autoimmune hepatitis (AIH). In scurfy liver, TNFα and fibrosis-related transcripts including Col1a1, Timp1, Acta2, Mmp2, and Mmp9 were upregulated. The level of proinflammatory monocytic macrophages (Ly-6Chi) was increased, while M2-type macrophages (CD206+) were downregulated compared to wildtype controls. Despite severe hepatic inflammation, fibrosis did not develop within 25 days, which is close to the lifespan of scurfy mice.DiscussionOur findings suggest that Treg-deficient scurfy mice spontaneously develop clinical, serological, and immunopathological characteristics of AILD with overlapping features of PBC and AIH.